Introducing Buton Natural Rock Asphalt New Materials for Bitumen Mofification and Soil Stabilization - Gatot Rusbintardjo; Nur Izzi M. Yusoff; Arafat Sulaiman Yerro (JACEE (Journal of Advanced Civil and Environmental Engineering), 2018)
Abstract:The natural asphalt in the world which can be explored until today is Buton Natural Rock Asphalt (BNRA). The other natural asphalt like Trinidad Lake Asphalt   Based on survey conducted by Directorate General of Mining Ministry of Energy and Mineral Resources Republik of Indonesia, amount of 650 million ton of BNRA are found in Buton island, yet until 92 years since BNRA in Buton Island discover by Hetzel, a Dutch Geolog, only 3.4 ton  that have been explored to be used for road work. This paper reported the using of  BNRA to modify bitumen to improve their properties in order to resist  the high temperature rutting, and to stabilize clay soil, to  improve their strenght. Bitumen penetration grade 80/100 which will be modified was blend by 15 to 65% of BNRA in increments of 5% by weight of bitumen, and to stabilized clay soil, amount of 2% to 8% in increements of 2% BNRA by weight of soil was added. To determine Penetration Index (PI) of neat bitumen and alsobitumen modified with BNRA,  penetration at 250 Celcius and softening point test were conducted. Penetration Index is the parameter to measure the temperature susceptibility of binder. The test results show that ...